Genetic Programming of Hypertension - Ahn, Sun-Young; Gupta, Charu (Frontiers in Pediatrics, 2018)
The heritability of hypertension (HTN) is widely recognized and as a result, extensive studies ranging from genetic linkage analyses to genome wide association studies are actively ongoing to elucidate the etiology of both monogenic and polygenic forms of hypertension. Due to the complex nature of essential HTN, however, single genes affecting blood pressure variability remain difficult to isolate and identify, and have rendered the development of single-gene targeted therapies challenging. The roles of other causative factors in modulating blood pressure, such as gene-environment interactions and epigenetic factors, are increasingly being brought to the forefront. In this review, we discuss the various monogenic HTN syndromes and corresponding pathophysiologic mechanisms, the different methodologies employed in genetic studies of essential HTN, the mechanisms for epigenetic modulation of essential HTN, pharmacogenomics and HTN, and finally, recent advances in genetic studies of essential HTN in the pediatric population.